1995
DOI: 10.1182/blood.v86.3.1184.1184
|View full text |Cite
|
Sign up to set email alerts
|

Human mononuclear phagocyte inducible nitric oxide synthase (iNOS): analysis of iNOS mRNA, iNOS protein, biopterin, and nitric oxide production by blood monocytes and peritoneal macrophages

Abstract: Nitric oxide (NO) is produced by numerous different cell types, and it is an important regulator and mediator of many processes including smooth muscle relaxation, neurotransmission, and murine macrophage- mediated cytotoxicity for microbes and tumor cells. Although murine macrophages produce NO readily after activation, human monocytes and tissue macrophages have been reported to produce only low levels of NO in vitro. The purpose of this study was to determine if stimulated human mononuclear phagocytes produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
112
1
2

Year Published

1996
1996
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 384 publications
(117 citation statements)
references
References 51 publications
2
112
1
2
Order By: Relevance
“…Important differences were noted between human and murine mononuclear phagocytes. For example, resting murine Mφ or Mφ‐like cell lines produce more NO than maximally activated human counterparts 37,38 . In addition, varying results on murine DC exist 39,40 and bovine Mφ and DC were previously analysed by PCR only 41 .…”
Section: Resultsmentioning
confidence: 99%
“…Important differences were noted between human and murine mononuclear phagocytes. For example, resting murine Mφ or Mφ‐like cell lines produce more NO than maximally activated human counterparts 37,38 . In addition, varying results on murine DC exist 39,40 and bovine Mφ and DC were previously analysed by PCR only 41 .…”
Section: Resultsmentioning
confidence: 99%
“…The antitumor activity of monocytes/macrophages in experimental rodent systems has been linked to high production of nitric oxide (NO) by activated macrophages (36) . On the other hand, human monocytes/macrophages (peripheral blood monocytes or peritoneal macrophages) are known to produce NO in quantities often around the limit of detection (45) .…”
Section: Non‐specific Defense Mechanisms In the Peritoneal Cavitymentioning
confidence: 99%
“…IFN‐γ is a potent monocyte activator, capable of inducing both cytotoxic and cytostatic activity of monocytes/macrophages and increasing the antigen‐presenting function of these cells (35,37,38) . The antitumor efficacy of macrophages is associated with inducible nitric oxide synthase (iNOS) in rodent macrophages, but the role of iNOS and nitric oxide (NO) in the antitumor activity of human monocytes/macrophages is still under discussion (45) . In humans, the induction by IFN‐γ of indoleamine 2,3‐dioxygenase (IDO), an enzyme catalyzing the synthesis of kynurenine from tryptophan may be more important.…”
Section: Immunotherapeutic Strategies Aimed At the Peritoneal Cavity mentioning
confidence: 99%
“…Both NOS 23 and HLA‐G are expressed in the placenta. In several diseases, such as coeliac disease, multiple sclerosis and HIV infection, HLA‐G 24–27 and iNOS 28–30 expression gives rise both to an increase in circulating HLA‐G and to protein nitration. It has been shown that NO can influence the function of some tolerogenic molecules such as the enzyme indoleamine 2,3‐dioxygenase 31 .…”
Section: Introductionmentioning
confidence: 99%